1995
DOI: 10.1161/01.res.76.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Sensitive Hypertension in Transgenic Mice Overexpressing Na + -Proton Exchanger

Abstract: Essential hypertension is one of the most common diseases that exacerbate the risk of cardiovascular or cerebrovascular attacks. Although the etiology of essential hypertension remains unclear, recent investigations have revealed that an enhancement of Na(+)-proton (Na(+)-H+) exchange activity is a frequently observed ion transport abnormality in hypertensive patients and animal models. To test the hypothesis that increased Na(+)-H+ exchange causes hypertension, we produced transgenic mice overexpressing Na(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Discovered by Kuro-o et al (1995) during the development of hypertensive transgenic mice models, the KLOTHO gene, a new anti-aging gene (Wang and Sun, 2009), has recently attracted considerable attention from researchers around the world (Kuro-o, 2009). The identification of SNPs in the human KLOTHO gene is currently one of the most active areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…Discovered by Kuro-o et al (1995) during the development of hypertensive transgenic mice models, the KLOTHO gene, a new anti-aging gene (Wang and Sun, 2009), has recently attracted considerable attention from researchers around the world (Kuro-o, 2009). The identification of SNPs in the human KLOTHO gene is currently one of the most active areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Transgenic mouse models of hypertension have also been developed through the overexpression of genes such as the sodium hydrogen exchanger or, from our own laboratory, the human renin and human angiotensinogen genes. 7,8 Although these mouse models have proven useful to better understand some of the underlying mechanisms of hypertension and vascular disease, it is important to be aware that the genetic background of the mice used to generate these models may influence the observed phenotype. As an example, Schlager and Weibust, 9 using the tail-cuff method, observed a wide range of blood pressure among 15 different inbred mouse strains.…”
mentioning
confidence: 99%
“…Different investigators have demonstrated enhanced NHE isoform-1 (NHE-1) activity in several blood cell lines of patients with essential hypertension compared with normotensive control subjects, 1,2 and transgenic mice that overexpress a recombinant NHE protein developed salt-sensitive hypertension. 3 Siffert et al 4 have demonstrated that immortalized B lymphoblasts of patients with essential hypertension, which display enhanced NHE-1 activity, also showed increased activity of pertussis toxin-sensitive G proteins. Variations in NHE-1 transcripts could not be detected, 5 and polymorphisms in genes that encode the subunits of trimeric G proteins, such as G␣ i2 , G␣ i3 , G␤ 1 , and G␤ 2 , 6 have been ruled out.…”
mentioning
confidence: 99%